2014
DOI: 10.17576/jskm-2015-1202-04
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Mempengaruhi Paras Kromium dalam Kalangan Petani di Daerah Bachok dan Pasir Puteh, Kelantan

Abstract: , sikap dan amalan (KAP) yang telah divalidasi untuk informasi berkaitan data demografi k. Sampel kuku dan rambut telah dianalisia dengan menggunakan kaedah pencernaan asid dan Inductively Coupled Plasma Mass Spectroscopy (ICPMS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…High levels of chromium in the hair of farmers who were hyperglycemic could also have been caused by external contamination, such as shampoo use (Jeejeebhoy, 1994). Study among farmers in Kelantan showed no significant difference of chromium levels between gender, age groups, and glucose level and diet intake (Nurfariha, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of chromium in the hair of farmers who were hyperglycemic could also have been caused by external contamination, such as shampoo use (Jeejeebhoy, 1994). Study among farmers in Kelantan showed no significant difference of chromium levels between gender, age groups, and glucose level and diet intake (Nurfariha, 2014).…”
Section: Discussionmentioning
confidence: 99%